Dynamics of Regional Head Elections (Pilkada) in 2020 During the COVID-19 Pandemic - Mudir Johan; Andi Wahyudi; Irawati Irawati (JOELS: Journal of Election and Leadership, 2021)
This research examines the problems of regional head elections (pilkada) as a government system that places the people as the sole voters. Pilkada is defined as the General Election to elect pairs of candidates for Regional Head proposed by a Political Party (Parpol) or a combination of political parties and individuals. But the problem is that the implementation of the pilkada in the COVID-19 pandemic has threatened the health of the people and has an impact on the weakening of various sectors, with this situation several agendas in the process of the pilkada stages were violated by candidate pairs such as not implementing health protocols at every stage of registration so that in the 2020 election feels threatened.